Probiotics for the improvement of metabolic profiles in patients with metabolic-associated fatty liver disease: A systematic review and meta-analysis of randomized controlled trials - Wang, Qiuhong; Wang, Ze; Pang, Boxian; Zheng, Huijuan; Cao, Zhengmin; Feng, Chunpeng; Ma, Wenxin; Wei, Junping (Frontiers in Endocrinology, 2022)
Objective.This meta-analysis of randomized controlled trials (RCTs) was conducted to assess the efficacy of probiotic in the treatment of metabolic associated fatty liver disease（MAFLD）mainly from the aspects of liver function,glycolipid metabolism and inflammation. Methods.Randomized controlled trials (RCTs) were searched through PubMed, Web of Science, Embase, the Cochrane Library until June 2022.Meta-analysis was performed on the therapeutic efficacy of liver function, glycolipid metabolism and inflammatory biomarkers by using the RevMan 5.4 software. Results. A total of 772 patients from 15 studies were identified for analysis.The methodological quality varied across studies.We found that adding probiotic therapies could reduce ALT(MD:-11.76[-16.06,-7.46],p<0.00001),AST(MD:-8.98[-13.16,-4.80],p<0.0001),GGT(MD:-5.63[-6.75,-4.51],p<0.00001),HOMA-IR(MD:-0.68[-1.15,-0.22],p=0.004)，LDL-c(MD:-0.33[-0.52,-0.14],p=0.0006) CRP((MD:-1.20[-2.35,-0.06],p=0.04) in MAFLD patients,as compared with the control group.However, there was no statistically significant improvement in the levels of TC,TG and TNF-ɑ among patients with MAFLD.Subgroup analyses showed that other key factors, such as age,participants’baseline body mass index (BMI),the duration of intervention may had an effect of probiotic therapies on outcomes. Conclusion. There is encouraging evidence that probiotics supplement may reduce liver enzyme levels,regulate glycolipid metabolism, and reduce inflammation reaction in MAFLD patients.This delineate novel therapeutic perspectives of probiotics.More rigorous and long-term trials are warranted to confirm the results.